1999
DOI: 10.1103/physreve.59.5881
|View full text |Cite
|
Sign up to set email alerts
|

Frictional mechanics of wet granular material

Abstract: The mechanical response of a wet granular layer to imposed shear is studied experimentally at low applied normal stress. The granular material is immersed in water and the shear is applied by sliding a plate resting on the upper surface of the layer. We monitor simultaneously the horizontal and the vertical displacements of the plate to submicron accuracy with millisecond time resolution. The relations between the plate displacement, the dilation of the layer and the measured frictional force are analyzed in d… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

10
95
1

Year Published

2000
2000
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(106 citation statements)
references
References 12 publications
10
95
1
Order By: Relevance
“…Clues may also be extracted from stick-slip motion of confined granular systems under shear, where numerical simulations (33,34) and some experiments (35)(36)(37) suggest that fluidization and dilation may play a role in the stick-slip instability. While this is suggestive, differences between granular layers and lubricant films include not only five orders of magnitude between size of grains and of molecules but, in particular, the issue of molecular interactions, negligible in granular shear but all-important when shearing lubricants.…”
mentioning
confidence: 99%
“…Clues may also be extracted from stick-slip motion of confined granular systems under shear, where numerical simulations (33,34) and some experiments (35)(36)(37) suggest that fluidization and dilation may play a role in the stick-slip instability. While this is suggestive, differences between granular layers and lubricant films include not only five orders of magnitude between size of grains and of molecules but, in particular, the issue of molecular interactions, negligible in granular shear but all-important when shearing lubricants.…”
mentioning
confidence: 99%
“…The effect of the air humidity on sliding friction of sand has in particular been much discussed, the general consensus being that humidity leads to the condensation of water between the grains [10][11][12][13]. The breaking up of the water bridges during sliding is then believed to significantly increase the friction coefficient.…”
mentioning
confidence: 99%
“…If adding water to sand has an effect on friction, this should have consequential repercussions for, e.g., sand transport through pipes [6]. This is an important issue, since the transport and handling of granular materials is responsible for around 10% of the world energy consumption [7], and optimizing granular transport ultimately relies on understanding the friction between the granular system and the walls [8][9][10].…”
mentioning
confidence: 99%
“…Laboratory experiments on the frictional behavior of layers of granular rock confined between granite plates [5] [6], and of glass bead assemblies [21] have shown that sheared confined granular media obey standard friction lawsnamely, beyond a static threshold, τ 12 = −f τ 22 . However, the velocity dependence of the dynamic friction coefficient is not yet very clearly established.…”
Section: Symmetric Casementioning
confidence: 99%